Two-Dimensional Grouping Affects Perisaccadic Perception of Depth and Synchrony. (June 2014) - Aruga, Reiko; Saito, Hideo; Ando, Hideyuki; Watanabe, Junji
There is considerable evidence that, when visual stimuli are presented around the time of a saccade, spatial and temporal perceptions of them are distorted. However, only a small number of previous studies have addressed the perception of a visual image induced by a saccade eye movement (visual image that is dynamically drawn on the retina during a saccade at the speed of the eye movement). Here we investigated three-dimensional and temporal perceptions of the saccade-induced images and found that perceptual grouping of objects has a significant effect on the perceived depth and timing of the images.